Peran Usaha Micro Kecil dan Menengah dalam Meningkatkan Kesejahteraan (Studi pada Desa Picuan Satu) - Andika A Kawulur; Arie F. Kawulur; Joubert M Dame (Indo Publishing, 2025)
This study aims to describe the role of Micro, Small, and Medium Enterprises (MSMEs) in improving the welfare of the Picuan Satu Village community. The background of this study is based on the fact that MSMEs are the backbone of the village economy, impacting not only the economic aspects but also social and educational aspects. The study used a qualitative approach with descriptive methods. Data were collected through interviews with five key informants consisting of MSME actors, village officials, and the community, supplemented by observation and documentation studies. Data validation was strengthened through triangulation of sources, techniques, and methods. The results of the interviews indicate that MSMEs in Picuan Satu Village have played a significant role in increasing community income, expanding employment opportunities, and utilizing local potential more productively. Informants stated that MSMEs help encourage community independence, reduce unemployment rates, and support family economic needs. However, various obstacles remain, such as limited capital, lack of managerial skills, and limited market access. Several informants emphasized the need for further support from the government and related institutions to develop business capacity and expand marketing networks. The study shows that the role of MSMEs not only impacts economic welfare but also creates broader social change. The presence of MSMEs encourages collaboration between communities, village governments, and local industry players in building economic independence. These findings align with previous research that emphasized MSMEs as a crucial instrument in sustainable village development. This study emphasizes that MSME empowerment strategies through access to capital, entrepreneurship training, and strengthening marketing networks need to be improved to ensure the economic sustainability of rural communities.